2018
DOI: 10.1016/j.jceh.2017.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sofosbuvir Plus Daclatasvir in Hepatitis C Virus Genotype-4 Patients: Promising Effect on Liver Fibrosis

Abstract: Sofosbuvir plus daclatasvir, with or without ribavirin achieved high efficacy and safety in HCV genotype 4 patients. Their effects were accompanied with attenuation of liver fibrosis. Further wider-scale studies are needed to evaluate the actual role of IL18 polymorphisms in treatment response with sofosbuvir/daclatasvir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 29 publications
5
7
0
Order By: Relevance
“…Interestingly, the present study showed a significant effect of SOF/DAV based regimen on liver fibrosis, that was significantly decreased at end of the treatment than at baseline ( P = 0.001). Similar results were reported in Egypt with the same regimen and also in Japan with DAV‐based regimen in HCV‐G1 patients that suggest that this regimen may decrease the incidence of HCC. Further studies are needed to show whether DAA combinations, including SOF/DAV based regimen, can prevent HCC, and to detect whether the improvement of the fibrosis is caused by the effect of drugs or due to eradication of virus.…”
Section: Discussionsupporting
confidence: 81%
“…Interestingly, the present study showed a significant effect of SOF/DAV based regimen on liver fibrosis, that was significantly decreased at end of the treatment than at baseline ( P = 0.001). Similar results were reported in Egypt with the same regimen and also in Japan with DAV‐based regimen in HCV‐G1 patients that suggest that this regimen may decrease the incidence of HCC. Further studies are needed to show whether DAA combinations, including SOF/DAV based regimen, can prevent HCC, and to detect whether the improvement of the fibrosis is caused by the effect of drugs or due to eradication of virus.…”
Section: Discussionsupporting
confidence: 81%
“…[ 34 ] Furthermore, liver fibrosis after DAA treatment improved in patients harbouring HCV GT 4 and in CHC patients with or without an HIV coinfection. [ 35 , 36 ] Concurrently, the present results indicate that non-invasive measurements of liver fibrosis, APRI index, and FIB-4 score were gradually reduced when patients achieved SVR12 after DAA therapy, suggesting that eradication of HCV may be responsible for decreased APRI and FIB-4 score. These scores were improved significantly upon laboratory investigation owing to normalization of liver enzymes after treatment.…”
Section: Discussionsupporting
confidence: 68%
“…IFN‐free regimens have shown to give better results . Sofosbuvir and daclatasvir in combination had shown safety and efficacy in HCV G4 patients with attenuation of liver fibrosis despite the combination's higher direct cost when compared with PEG IFN‐RBV regimen …”
Section: What Is Known and Objectivementioning
confidence: 99%